Adjusting to Europe : the Impact of the European Union on National Institutions. - Meny, Yves (European public policy series., 1996)
Examines policy-making at EU-level; explores how three major nation-states have adapted their policy processes and institutions to the European challenge; and focuses on the impact of the EU on industrial, competition and social policies.